Philosophy of mind A-Z - Rakova, Marina, 1973- (Philosophy A-Z series., 2006)
Containing entries on historical and contemporary figures, this book explains the importance of the debates and how the field has been shaped. It includes a range of philosophy of mind, from Plato and Leibniz to externalism and the frame problem, from Husserl to neural Darwinism, and from mental causation to the problem of consciousness.